2010
DOI: 10.1111/j.1439-0450.1981.tb01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility of Escherichia coli from Domestic Fowl

Abstract: Resistance of E. coli to antibiotics is not only an obstacle for the control of this infection but also provides conditions for the transfer of drug resistance factors to other enterobacteria (1). The presence of drug resistant E. coli in the fowl slaughtered for meat is of public health significance (4). Because of the concentration of poultry population around Ludhiana E. coli infections among domestic fowl are on the increase and drug resistant strains are often isolated from E. coli infections. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, research is urgently needed given the projected large-scale increase in poultry production and antimicrobial use in the poultry sector ( Brahmachari et al 2013 ; Van Boeckel et al 2015 ). Sarma et al ( 1981 ) isolated E. coli from healthy and diseased fowl in Ludhiana, Punjab, India, and discovered that approximately 80% of isolates were resistant to chlortetracycline, tetracycline, oxytetracycline, and triple sulfas. Shivachandra et al ( 2004 ) found 100% resistance to sulfadiazine and widespread resistance to amikacin, carbenicillin, erythromycin, and penicillin in Pasteurella multocida isolates from chickens and other birds from 11 separate states in India.…”
Section: Discussionmentioning
confidence: 99%
“…However, research is urgently needed given the projected large-scale increase in poultry production and antimicrobial use in the poultry sector ( Brahmachari et al 2013 ; Van Boeckel et al 2015 ). Sarma et al ( 1981 ) isolated E. coli from healthy and diseased fowl in Ludhiana, Punjab, India, and discovered that approximately 80% of isolates were resistant to chlortetracycline, tetracycline, oxytetracycline, and triple sulfas. Shivachandra et al ( 2004 ) found 100% resistance to sulfadiazine and widespread resistance to amikacin, carbenicillin, erythromycin, and penicillin in Pasteurella multocida isolates from chickens and other birds from 11 separate states in India.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials are used extensively in food animal production for disease prevention, treatment and growth promotion. Sarma et al (1981) discovered that approximately 80% of isolated E. coli from healthy and diseased poultry was resistant to chlortetracycline, tetracycline, oxytetracycline and triple sulfas. Similarly, Paula Signolfi et al (2019) found that more than 67% of isolated Escherichia coli were resistant to tetracycline, nalidixic acid and ampicillin.…”
Section: Discussionmentioning
confidence: 99%